Silk peptide treatment potentiates natural killer cell activity in vitro and induces natural killer cell maturation and activation in mouse splenocytes. (1st January 2019) - Jang, Sun-Hee; Oh, Mi-Sun; Baek, Hyang-Im; Ha, Ki-Chan; Lee, Jeong-Yong; Jang, Yong-Suk
Abstract: Context: Silk peptide from cocoons of silkworm ( Bombyx mori L., Bombycidae) has been employed as a biomedical material and exhibits various bioactivities, including immune-modulating activity. Objective: We analyzed whether silk peptide exerts direct modulating effects on NK cells using an NK cell line in vitro and ex vivo splenocytes. We also attempted to delineate the mechanism underlying the modulation. Material and methods: In vitro activity of silk peptide on NK cells was determined by measurement of cytolytic activity against K562 cells at an effector-to-target ratio of 5:1 after incubation of NK-92MI cells with silk peptide (0–2000 μg/mL) for 48 and 72 h. Ex vivo activity of silk peptide on mouse splenic NK cells was determined similarly by using YAC-1 cells. Results: Treatment of NK-92MI NK cells with silk peptide (500–2000 μg/mL) significantly increased cytolytic activity on target cells by 2- to 4-fold. The same concentrations (500–2000 μg/mL) of silk peptide treatment also significantly enhanced the cytolytic activity of splenic NK cells against YAC-1 cells. Silk peptide treatment of IL-2-stimulated splenocytes induced enhanced expression of Th1, 2 and 17 cytokines including TNF-α, IFN-γ, IL-6, IL-4 and IL-17. Finally, ex vivo treatment with silk peptide on mouse splenocytes significantly enhanced the degree of NK cell maturation in a dose-dependent manner from 3.49 to 23.79%. Discussion and conclusions: These findings suggest that silk peptide stimulates NK cells, thereby influencing systemic immune functions and improving natural immunity. Thus, silk peptide could be useful as a complementary therapy in cancer patients.